Degradation of Glyphosate in Water by Electro-Oxidation on Magneli Phase: Application to a Nanofiltration Concentrate - Wiyao Maturin Awesso; Ibrahim Tchakala; Sophie Tingry; Geoffroy Lesage; Julie Mendret; Akpénè Amenuvevega Dougna; Eddy Petit; Valérie Bonniol; Mande Seyf-Laye Alfa-Sika; Marc Cretin (Molecules)
This study evaluates the efficiency of sub-stoichiometric Ti4O7 titanium oxide anodes for the electrochemical degradation of glyphosate, a persistent herbicide classified as a probable carcinogen by the World Health Organization. After optimizing the process operating parameters (pH and current density), the mineralization efficiency and fate of degradation by-products of the treated solution were determined using a total organic carbon (TOC) analyzer and HPLC/MS, respectively. The results showed that at pH = 3, glyphosate degradation and mineralization are enhanced by the increased generation of hydroxyl radicals (●OH) at the anode surface. A current density of 14 <semantics>mA cm−2</semantics> enables complete glyphosate removal with 77.8% mineralization. Compared with boron-doped diamond (BDD), <semantics>Ti4O7</semantics> shows close performance for treatment of a concentrated glyphosate solution (0.41 mM), obtained after nanofiltration of a synthetic ionic solution (0.1 mM glyphosate), carried out using an NF-270 membrane at a conversion rate (Y) of 80%. At 10<semantics> mA cm−2</semantics> for 8 h, <semantics>Ti4O7</semantics> achieved 81.3% mineralization with an energy consumption of 6.09 <semantics>kWh g−1</semantics> TOC, compared with 90.5% for BDD at 5.48 <semantics>kWh g−1</semantics> TOC. Despite a slight yield gap, <semantics>Ti4O7</semantics> demonstrates notable efficiency under demanding conditions, suggesting its potential as a cost-effective alternative to BDD for glyphosate electro-oxidation.